Antibacterial properties of root canal lubricants: A comparison with commonly used irrigants. (16th September 2014) - Wong, Samantha; Mundy, Lance; Chandler, Nicholas; Upritchard, Jenine; Purton, David; Tompkins, Geoffrey
Abstract The aim was to assess in vitro the antibacterial activity of 10 root canal lubricants. K‐Y Jelly personal lubricant, RC‐Prep, File‐Eze, File‐Rite, EndoPrep Gel, Endosure Prep Crème 15%, Prep‐Rite, Glyde, SlickGel ES and Alpha Glide were selected and compared in their antimicrobial properties to seven irrigants. Serial dilutions of each agent in tryptic soy broth were inoculated with either Enterococcus faecalis or Pseudomonas aeruginosa and incubated at 37C for 24 h. During incubation bacterial growth was measured by optical density (A600), and samples removed for cultivation on tryptic soy broth agar. Against both test bacteria after 1 h incubation, six lubricants recorded minimum bactericidal concentrations ranging from 1/10 to 1/80, whereas the inhibitory activity of the irrigants ranged from 1/20 to 1/640. Under these conditions, several lubricants exhibited antimicrobial activity comparable with some irrigants. Three irrigants, Consepsis (containing chlorhexidine), Endosure EDTA/C (containing cetrimide) and EndoPrep Solution (containing cetrimide), showed superior antibacterial action to lubricants against both species. The irrigants containing ethylenediamine tetraacetic acid and cetrimide were the most effective against both bacterial species at all time intervals. Antimicrobial activity of the lubricants did not correlate to pH values, which ranged from 2.9 to 10.3. Root canal lubricants have antibacterial properties that may help to disinfect canals.